PENJADWALAN PRODUKSI PIPA DI T SINAR UTAMA NUSANTARA MEDAN - Endro Prihastono; Moh. Irshad Ibad (Jurnal Ilmiah Dinamika Teknik, 2018)
Production scheduling is a measuring tool for facility planning, worker and equipments that is done sorting work on each processing with the aim of optimization. The purpose of this research is how the production scheduling at PT. Sinar Utama Nusantara can run well to meet the needs of the pipe. From the results of the observation can be concluded that PVC production is done in several machines that are assembled in one production line, PT. Sinar Utama Nusantara not only produces PVC pipes but also other products such as HDPE Pipes, and Gutters and Production PT. Sinar Utama Nusantara implements the production of make to stock, with a daily production capacity of 30 tons. Keywords: Scheduling, Production.